Carotenoid compounds in grapes and their relationship to plant water status - Oliveira, C. (2011)
The aim of this work was to study the relationship between carotenoid contents in grapevine berries and plant water status. For this purpose, a black grapevine variety, Vitis vinifera L. cv. Touriga Nacional, was studied. The experiments were carried out in the same Douro vineyards, with plants of the same age, in two different water retention soils. A higher water retention capacity soil, soil A, and a lower water retention capacity soil, soil B, were both in a 1.2 m deep silt-loam schist-derived soil. The training system was the double cordon trained and spur pruned. A first range was nonirrigated (NI) and a second one was irrigated (I), 60% of evapotranspiration (ET0). For soil B, a 30% of ET0 treatment was also applied. The plant water status was estimated by predawn leaf water potential. The effects of plant water status on berry growth were studied by measurement of the berry weight and total soluble solids (°Brix). The carotenoid profile was quantitatively determined by high-performance liquid chromatography/diode array. Carotenoids determined were â-carotene, lutein, neoxanthin, violaxanthin, and luteoxanthin. The comparison between irrigated and nonirrigated grapes was followed from 2 weeks before veraison until the ripe stage. Results showed that at harvest time, berries exposed to the NI had a lower weight than those exposed to the irrigated treatment (60% of ET0), 0.89 vs 1.36 g/berry and 0.94 vs 1.34 g/berry, for soils A and B, respectively. The irrigated treatment contributed to a higher sugar concentration in both soils. However, depending on the soil water retention capacity, the carotenoid contents were different in soils A and B. For soil A, the total carotenoid content was similar for both NI and I treatments. However, with regard to soil B, in irrigated treatment, levels of carotenoids were approximately 60% lower than those found for the NI. It seems to be possible to produce higher weight berries (with higher sugar levels) with similar carotenoid contents. On the other hand, soil characteristics had a larger influence than irrigation on the concentration of carotenoids in grapes, resulting in an important viticultural parameter to take into account in aroma precursor formation.